Publication anxiety in academia: Development and psychometric validation of a three-dimensional scale - Deroncele-Acosta, Angel (Revista de Ciencias Sociales, 2026)
In contemporary academia, the publish or perish culture has intensified psychological pressure on researchers, making scientific publication a key source of evaluation and symbolic validation. However, Publication Anxiety remains a poorly operationalized and insufficiently measured phenomenon in empirical research. This study aimed to design and psychometrically validate the Publication Anxiety Scale-PAS to assess publication-related anxiety among university faculty, based on a three-dimensional model comprising Manuscript Preparation, Author’s Editorial Management, and Scientific Impact. A quantitative, instrumental, and cross-sectional design was applied. The sample consisted of 171 university faculty members. The PAS, composed of 12 items with a Likert-type response format, was administered online. Psychometric analyses included descriptive statistics, internal consistency, exploratory and confirmatory factor analyses, and multigroup invariance testing by sex. The results supported a robust three-factor structure with adequate goodness-of-fit indices. The scale showed satisfactory internal consistency and factorial validity. Multigroup analyses indicated general measurement invariance, with some differences in factor intensity between men and women. The PAS is a valid and reliable instrument for university faculty. Its application provides relevant evidence for understanding academic well-being and offers a valuable tool for informing institutional policies on research evaluation, mental health promotion, and sustainable scientific productivity within higher education systems.